Analisis Karakteristik Elektrik Zno Terdoping Cr2O3 Untuk Aplikasi Varistor Tegangan Rendah - Henry B. H. Sitorus; Dwi Asmi; Saka Sandaran (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
ZnO is one of the main ingredients of making varistor can be used as a protective device to protect electronic and electrical equipment from the dangers of impulse over voltage. Ability to function as a varistor protective because ZnO has a resistance that is not linear. When the system did not experience over voltage fault, current does not flow from the varistor, but when over voltage fault on system, current will flow from the fault line to the ground through varistor. The addition of dopant to ZnO expected to improve non-linierity of ZnO resitance. In this research used Cr2O3 as dopant. Varistor manufacturing using the dry pressing method at a pressure of 150 kg/cm2. Sintering process performed at a temperature of 900 degreeC with a time of detention for 2 hours. The size of the resulting varistor has a thickness 1.5 mm and 19 mm diameter. Characterization performed includes the analysis of crystal structures using X-ray diffraction, microstructure using MO and SEM, and electrical properties characterization volt-time using capacitive impulse voltage generator. Based on test results of x-ray diffraction and in accordance with PDF No. 38-1479 prove that the sample ZnCr5.0 contains Cr2O3 with ZnO compounds dominant. Microstructure obtained by SEM seems not so clear, it is because the process is not optimum preparation and etching is not performed on test samples. Pure ZnO Varistor can work cut given impulse voltage, whereas the varistor mixtures of ZnO-Cr2O3 can not work to cut the impulse voltage 900 V-1450 V provided, it is alleged to be caused sintering temperature given is not optimum and dopan provided is not sufficient to improve performance a varistor.